Enhancing College Students’ Achievement, Motivation, and Engagement in Film Character Design Through AI-Driven Smart Sketchpad: A Personalized Interactive Learning Model for Art Education - Siyuan Zeng; Norsafinar Rahim; Songni Xu (IEEE Access)
As technologies such as artificial intelligence rapidly evolve, the traditional lecture-based class can no longer meet students’ learning needs. Previous research has demonstrated that AI can be essential for improving the learning experience. However, research has also pointed out that promoting AI applications in education has been challenging. Developing domain-specific applications based on AI technology is a massive challenge for the development of AI in education. Further research has pointed out that the development of AI applications in education rarely considers students’ perceptual learning motivations. This study proposes a teaching method based on an artificial intelligence tool, the Artificial Intelligence Smart Sketchpad (AISS), to assist in teaching character art design in a multimedia environment. The artificial intelligence will identify students’ drawing sketches and make corrections. This study explores the impact of AISS on achievement, engagement, and motivation among film character art design students in a multimedia environment. To this end, we adopted a quantitative research method. Over five weeks, we assessed 60 university students. Research results indicate that the AI smart sketchpad (AISS) significantly improves students’ motivation, engagement, and performance. Student feedback suggests that AI stimulates creative thinking by offering greater creative freedom and possibilities and quickly transforming sketches into high-quality design drawings. A new direction will be explored for personalized and self-learning for students.